Peningkatan Keterampilan Menulis Artikel Ilmiah Mahasiswa Berbasis Artificial Intelligence melalui Modifikasi Prompt - Anhar Anhar; Haryadi Jaka Susila; Raihan Raihan; Sasi Septiani; Muthia Nadaul Riskiyah (Balai Bahasa Provinsi Bali, 2025)
This research aimed to enhance students' academic article writing skills through a metacognitive-based prompt modification framework to address the significant gap between AI technology adoption and the accuracy of AI responses in academic writing instruction. Specific research objectives included: (1) analyzing the effectiveness of each stage of prompt modification in improving the quality and relevance of AI responses, (2) developing an integrated systematic framework grounded in metacognitive knowledge that is adaptable to various learning contexts, and (3) evaluating the comprehensive impact of human-AI interaction on enhancing academic article writing skills and fostering critical cognitive awareness among students. The study employed qualitative methodology with an exploratory case study design involving all first-semester students at the School of Economics Balikpapan, Academic Year 2025/2026. Primary data were collected through comprehensive digital documentation of prompt modification responses and structured recording systems during implementation of a six-stage framework: pre-writing, draft development, prompt evaluation, modification with metadata synthesis, multi-stage implementation with metacognitive student intervention. Data analysis utilized a staged approach encompassing article categorization, contextual evaluation of content substance, and iterative processes to ensure publication-quality articles. The research findings demonstrate that prompt modification proved effective in transforming learning from spontaneous approaches toward structured guided discovery with significant improvements in coherent argumentation skills and systematic idea organization. Findings confirm the synergistic effect of integrating prompt engineering with metacognitive principles that optimize AI-based academic writing skills. The research contributes theoretically to developing culturally responsive pedagogy through contextual frameworks addressing the linguistic, cognitive, and cultural characteristics of Indonesian students, while providing evidence-based practical guidelines for implementing responsible AI integration in academic writing curricula within higher education institutions. AbstrakPenelitian ini bertujuan untuk meningkatkan keterampilan framework modifikasi prompt berbasis metakognitif untuk mengatasi gap signifikan antara penggunaan teknologi AI dengan tingkat akurasi jawaban AI dalam pembelajaran menulis artikel ilmiah mahasiswa. Tujuan spesifik penelitian meliputi: (1) menganalisis efektivitas setiap tahapan modifikasi prompt dalam meningkatkan kualitas dan relevansi jawaban AI, (2) mengembangkan framework sistematis terintegrasi pengatahuan metakognitif yang dapat diadaptasi berbagai konteks pembelajaran, dan (3) mengevaluasi dampak interaksi manusia dengan pemanfaat AI terhadap peningkatan keterampilan menulis artikel ilmiah dan peningkatan kesadaran kognitif yang harus ditingkatkan oleh mahasiswa. Penelitian menerapkan metodologi kualitatif dengan desain studi kasus eksploratif yang melibatkan seluruh mahasiswa semester I Sekolah Tinggi Ilmu Ekonomi Balikpapan tahun akademik 2025/2026. Data primer dikumpulkan melalui dokumentasi digital jawaban dari modifikasi prompt secara komprehensif dan sistem pencatatan terstruktur selama implementasi framework enam tahap: pra-penulisan, pengembangan draft, evaluasi prompt, modifikasi dengan sintesis metadata, implementasi multi-tahap dengan interfensi meta kofnitif mahasiswa. Analisis data menggunakan pendekatan bertahap dengan kategorisasi artikel, evaluasi kontekstual substansi konten, dan proses iteratif untuk artikel berkualitas yang telah dipublikasikan publikasi. Penelitian menunjukkan modifikasi prompt terbukti efektif mentransformasi pembelajaran dari pendekatan spontan menuju guided discovery yang terstruktur dengan peningkatan signifikan dalam keterampilan argumentasi koheren dan organisasi ide secara sistematis. Temuan mengkonfirmasi synergistic effect integrasi prompt engineering dengan metacognitive principles yang mengoptimalkan keterampilan menulis artikel ilmiah berbasi AI. Penelitian berkontribusi teoritis pada pengembangan culturally responsive pedagogy melalui contextual framework untuk karakteristik aspek linguistik kognitif mahasiswa Indonesia, serta menyediakan evidence based guidelines praktis bagi implementasi responsible AI integration dalam kurikulum penulisan akademik perguruan tinggi.